Science teachers’ knowledge, attitudes and skills as determinants of classroom practices in entrepreneurship education in senior secondary schools in Lagos, Nigeria - BAMIKOLE OLUDARE OGUNLEYE (Annual Journal of Technical University of Varna, 2019)
Entrepreneurship behaviour is a 21st century attribute required for transforming the industrial and employment space into productive ones. Science students are critical towards the achievement of these requirements. To ensure quality entrepreneurship education, science teachers’ entrepreneurship background and characteristics become germane. This study, therefore, investigated the extent to which science teachers’ entrepreneurship knowledge, attitudes and skills determine their classroom practices in entrepreneurship education in selected Senior Secondary Schools in Lagos, Nigeria. The correlational type of the cross-sectional descriptive research design was adopted. A purposively selected sample of 245 SS2 Science teachers from thirty schools in Lagos mainland, Nigeria participated in the study.  Instruments used were: Teacher Entrepreneurship Knowledge Test (r=.86), Teacher Entrepreneurship Attitudes Scale (r=.89), Teacher Entrepreneurship Skills Inventory (r=.85) and Classroom Practices Rating Scale (r=.89). Data were analysed using Pearson Product Moment Correlation and Multiple Regression. Findings showed strong and significant bivariate relationships between each of teachers knowledge (r=.59), attitudes r=.55), skills (r=.52) and classroom practices. The three factors jointly explained 46% of classroom practices with significant relative effects. Teachers require good knowledge, attitudes and skills for effective implementation of entrepreneurship programmes in science education, hence, they need to be exposed to in-service training in entrepreneurial studies.